Prevalence of Target Organ Damage in Chinese Hypertensive Children and Adolescents - Yang, Liu; Yang, Lili; Zhang, Yuanyuan; Xi, Bo (Frontiers in Pediatrics, 2018)
Abstract Background Subclinical target organ damage (TOD) has been common in hypertensive children, but there is limited data in Chinese pediatric population. This study aimed to investigate the prevalence of subclinical TOD in Chinese hypertensive children and adolescents. Methods A cross-sectional study was performed in children and adolescents from four schools in Jinan of China between September 2012 and September 2014. The hypertensive status was confirmed based on blood pressure measured on three different occasions. Those with hypertension were invited to participate in the evaluation of TOD (including heart, arteries, and kidney) and metabolic disorders. A total of 7840 children and adolescents aged 6-17 years were recruited at baseline, of whom 373 were diagnosed as hypertension after three separate visits, and 333 (89%) participated in evaluation of TOD. Results Among 333 hypertensive children, 47.4% had elevated carotid intima-media thickness, 32.4% had left ventricular hypertrophy, 29.2% had dyslipidemia, 7.6% had liver dysfunction, and 4.1% had microalbuminuria. Cardiovascular damages were more prevalent in children aged 9-14 years than the other age groups (i.e., 6-8 and 15-17 years). Girls had higher proportion of microalbuminuria than boys (8.2% vs. 2.6%). No significant sex and age differences were observed for the prevalence of other TODs. Nearly all subclinical TODs were much more prevalent in hypertensive children with overweight and obesity than those with normal weight, except microalbuminuria. Conclusions The subclinical TOD is prevalent in Chinese hypertensive children and adolescents. Effective measures should be taken to fight against the subclinical TOD.